New species of Coccidella Hambleton and Rhizoecus Kunckel d’Herculais from South America (Hemiptera: Rhizoecidae) - Schneider, Scott A.; Lapolla, John S. (Zootaxa, 2024)
Two new species of root mealybugs (Hemiptera: Rhizoecidae) from South America are described and illustrated based on the morphology of the adult females: Coccidella advena Schneider & LaPolla, sp. nov. from Peru and Rhizoecus peripotaro Schneider & LaPolla, sp. nov. from Guyana and Peru. Both species were collected with colonies of Acropyga ants (Hymenoptera: Formicidae) but only R. peripotaro was found to be trophobiotic; C. advena was ignored by the ants and is considered to be free-living. A guide to aid in identification is provided for each species.